Recreational and sports activity of prison system employees in Poland in the interwar period - Renata Urban (Jan Długosz University in Częstochowa, 2019)
The aim of the article is to discuss conditions for the development and a presentation of achievements in the field of recreational and sports activity of Prison Officers Poland in the interwar period. When Poland regained independence in 1918, it mobilized many representatives of professional groups (the police, the military, the prison staff) to take the initiative of creating trade associations. Their main task was comprehensive help, medical care and concern for the preservation of health by organizing activities in the field of recreation and sports. In January 1919, representatives of the penitentiaries established the Prison Guards and Officers Association renamed soon the Prison Officers Association of the Republic of Poland. Recognizing the importance of physical activity for the proper development of the organism and the need to recover after exhausting work, the Association came up with a project of building health and medical resorts and creating boathouses, as well as establishing sports clubs and organizing sports competition. Initially, the activities in this field developed slowly but gradually the action involved more and more branches of the Association in prisons throughout the country. By the end of the 30s of the twentieth century, the state of health spa infrastructure, recreation and sports had reached a satisfactory level and the rules of sporting competition had been established.